Fetal weight estimation at term – ultrasound versus clinical examination with Leopold’s manoeuvres: a prospective blinded observational study - Preyer, Oliver; Husslein, Heinrich; Concin, Nicole; Ridder, Anna; Musielak, Maciej; Pfeifer, Christian; Oberaigner, Willi; Husslein, Peter (BMC pregnancy and childbirth, 2019)
Background Fetal weight estimation is of key importance in the decision-making process for obstetric planning and management. The literature is inconsistent on the accuracy of measurements with either ultrasound or clinical examination, known as Leopold’s manoeuvres, shortly before term. Maternal BMI is a confounding factor because it is associated with both the fetal weight and the accuracy of fetal weight estimation. The aim of our study was to compare the accuracy of fetal weight estimation performed with ultrasound and with clinical examination with respect to BMI. Methods In this prospective blinded observational study we investigated the accuracy of clinical examination as compared to ultrasound measurement in fetal weight estimation, taking the actual birth weight as the gold standard. In a cohort of all consecutive patients who presented in our department from January 2016 to May 2017 to register for delivery at ≥37 weeks, examination was done by ultrasound and Leopold’s manoeuvres to estimate fetal weight. All examiners (midwives and physicians) had about the same level of professional experience. The primary aim was to compare overall absolute error, overall absolute percent error, absolute percent error > 10% and absolute percent error > 20% for weight estimation by ultrasound and by means of Leopold’s manoeuvres versus the actual birth weight as the given gold standard, namely separately for normal weight and for overweight pregnant women. Results Five hundred forty-three patients were included in the data analysis. The accuracy of fetal weight estimation was significantly better with ultrasound than with Leopold’s manoeuvres in all absolute error calculations made in overweight pregnant women. For all error calculations performed in normal weight pregnant women, no statistically significant difference was seen in the accuracy of fetal weight estimation between ultrasound and Leopold’s manoeuvres. Conclusions Data from our prospective blinded observational study show a significantly better accuracy of ultrasound for fetal weight estimation in overweight pregnant women only as compared to Leopold’s manoeuvres with a significant difference in absolute error. We did not observe significantly better accuracy of ultrasound as compared to Leopold’s manoeuvres in normal weight women. Further research is needed to analyse the situation in normal weight women.